2021
DOI: 10.3390/medicina57101015
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Regeneration and Function in Sports: A Focus on Vitamin D

Abstract: Muscle is one of the main targets for the biological effects of vitamin D. This hormone modulates several functions of skeletal muscles, from development to tissue repair after injury, through genomic and non-genomic mechanisms. Vitamin D deficiency and supplementation seem to significantly affect muscle strength in different populations, including athletes, although optimal serum 25(OH)D3 level for sport performance has not been defined so far. Additionally, vitamin D deficiency results in myopathy characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Consistent with our results, Pilch et al, [ 23 ] and Choi et al, [ 24 ] reported that vitamin D improves EAE-induced skeletal muscle cell damage. Vit D modulates several functions of skeletal muscles via increasing the expression of myogenic factors in satellite cells, enhancing muscle differentiation, growth, and regeneration, modulating myostatin via increased follistatin expression, modulating phosphate metabolism by affecting mitochondrial health via modulating calcium metabolism, thus reducing the muscle injury and increasing the recovery from EAE sessions [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our results, Pilch et al, [ 23 ] and Choi et al, [ 24 ] reported that vitamin D improves EAE-induced skeletal muscle cell damage. Vit D modulates several functions of skeletal muscles via increasing the expression of myogenic factors in satellite cells, enhancing muscle differentiation, growth, and regeneration, modulating myostatin via increased follistatin expression, modulating phosphate metabolism by affecting mitochondrial health via modulating calcium metabolism, thus reducing the muscle injury and increasing the recovery from EAE sessions [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optimal vitamin D levels suppress inflammatory reactions by helping to maintain adequate levels of appropriate anti-inflammatory cytokines (mainly TNF-α and interleukin-10) [ 14 ]. In addition, by activating intracellular receptors, vitamin D increases the protein content of cells, increases muscle strength and endurance (maintaining proper ATP levels) [ 15 , 16 ], protects muscle fibers degeneration [ 17 ], and delays the onset of muscle pain and fatigue [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Again, the low daily dosages of vitamin D may be the cause of these unexpected results. Recently, Iolascon et al 57 investigated the effects of vitamin D on muscle tissue through genomic and non‐genomic pathways, concluding that vitamin D supplementation enhances the structural and functional restoration of the muscles, by increasing the expression of myogenic factors in satellite cells during recovery from muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, vitamin D was shown to support the healing of muscle tissue in rats subjected to crush injury and in humans experiencing exercise-induced muscle injury [42,43]. Given that the rapid changes between anabolism and catabolism in modern, high performing sows kept on a restricted protein supply include a periodic process of regeneration, different aspects regarding the mode of action that are currently under discussion have been reviewed recently by Iolascon et al [44].…”
Section: Musculoskeletal Systemmentioning
confidence: 99%